BASIC FINANCIAL AND INVESTMENT MODELS - Davranov Odil Jumanazarovich; Eshmuminova Dilbar Oral daughter (American Journals, 2023)
The article provides a general understanding of the main financial and investment models and the use of these models.
Keywords: model, innovation, investment, financial, process, use.